2020
DOI: 10.1021/acs.biochem.0c00574
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Lipid Binding to Yeast Niemann Pick Type C2 Protein

Abstract: Niemann Pick type C2 (NPC2) is a small sterol binding protein in the lumen of late endosomes and lysosomes. We showed recently that the yeast homologue of NPC2 together with its binding partner NCR1 mediates integration of ergosterol, the main sterol in yeast, into the vacuolar membrane. Here, we study the binding specificity and the molecular details of binding of a lipid to yeast NPC2. We find that NPC2 binds fluorescenceand spin-labeled analogues of phosphatidylcholine (PC), phosphatidylserine, phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Because titration experiments to assess sterol binding to proteins are typically carried out with DHE concentrations exceeding its CAC in aqueous buffer, sterol self-aggregation must be taken into account in such measurements, typically only providing apparent dissociation constants (discussed in refs and ). To assess sterol–protein interactions, if possible, FRET from aromatic residues of the protein to DHE should be employed as a readout for the binding event. ,,, Alternatively, the increase of DHE fluorescence upon its excitation at ∼330 nm in buffer can be employed as a readout for sterol binding to a given protein. ,,, The fluorescence spectrum of protein-bound DHE when excited at DHE’s maximal absorbance often resembles its spectrum in ethanol (i.e., in the monomeric form), suggesting that many sterol-binding proteins shift the equilibrium between monomer and sterol aggregate in aqueous solution. In fact, Schroeder and co-workers showed that sterol carrier protein 2 not only can bind DHE but also can extract DHE from aggregates in buffer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because titration experiments to assess sterol binding to proteins are typically carried out with DHE concentrations exceeding its CAC in aqueous buffer, sterol self-aggregation must be taken into account in such measurements, typically only providing apparent dissociation constants (discussed in refs and ). To assess sterol–protein interactions, if possible, FRET from aromatic residues of the protein to DHE should be employed as a readout for the binding event. ,,, Alternatively, the increase of DHE fluorescence upon its excitation at ∼330 nm in buffer can be employed as a readout for sterol binding to a given protein. ,,, The fluorescence spectrum of protein-bound DHE when excited at DHE’s maximal absorbance often resembles its spectrum in ethanol (i.e., in the monomeric form), suggesting that many sterol-binding proteins shift the equilibrium between monomer and sterol aggregate in aqueous solution. In fact, Schroeder and co-workers showed that sterol carrier protein 2 not only can bind DHE but also can extract DHE from aggregates in buffer .…”
Section: Discussionmentioning
confidence: 99%
“…63,67,68,73 Alternatively, the increase of DHE fluorescence upon its excitation at ∼330 nm in buffer can be employed as a readout for sterol binding to a given protein. 15,64,65,74 The fluorescence spectrum of protein-bound DHE when excited at DHE's maximal absorbance often resembles its spectrum in ethanol (i.e., in the monomeric form), suggesting that many sterol-binding proteins shift the equilibrium between monomer and sterol aggregate in aqueous solution. In fact, Schroeder and co-workers showed that sterol carrier protein 2 not only can bind DHE but also can extract DHE from aggregates in buffer.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…NPC2 from S. cerevisiae has demonstrated broad substrate selectivity (binding phosphatidylcholine, phosphatidylinositol and phosphatidylserine). Since the binding of hydrophobic substrates is primarily entropydriven and unspecific, scNPC2 can act as a general lipid solubilizer possibly interacting with several other membrane proteins to shuttle these compounds out of the vacuolar lumen [86,118]. Additionally, atypical NPC2 proteins are shown to shuttle a variety of different sterol types from algal symbionts to their Cnidarian hosts [119], whereas NPC2 from the Japanese carpenter ant has been implicated in binding non-sterol pheromones [83].…”
Section: Substrate Specificity Of Npc1/ncr1 and Npc2mentioning
confidence: 99%
“…We thus conclude that the NPC2-like proteins that are found in plant genomes are lipid transporters that are structurally similar to the fungal and animal NPC2s, but there is no evidence that they interact with NCR1 proteins. In fungi, NPC2 can bind to ergosterol as well as PI, PG and phosphatidylcholine 47 and appears to play a role as a multi-lipid transporter: a similar role is likely in plants.…”
Section: Npc1/ncr1 and Npc2-like Sites In Plantsmentioning
confidence: 99%